Atomic Insights of Self‐Healing in Silicon Nanowires. (26th December 2022) - Cui, Junfeng; Sun, Yang; Chen, Huixin; Yang, Yingying; Chen, Guoxin; Ke, Peiling; Nishimura, Kazuhito; Yang, Yong; Tang, Chun; Jiang, Nan
Abstract: The self‐healing capability is highly desirable in semiconductors to develop advanced devices with improved stability and longevity. In this study, the automatic self‐healing in silicon nanowires is reported, which are one of the most important building blocks for high‐performance semiconductor nanodevices. A recovery of fracture strength (10.1%) on fractured silicon nanowires is achieved, which is demonstrated by in situ transmission electron microscopy tensile tests. The self‐healing mechanism and factors governing the self‐healing efficiency are revealed by a combination of atomic‐resolution characterizations and atomistic simulations. Spontaneous rebonding, atomic rearrangement, and van der Waals attraction are responsible for the self‐healing in silicon nanowires. Additionally, the self‐healing efficiency is affected by the fracture surface roughness, the nanowire size, the nanowire orientation, and the passivation of dangling bonds on fracture surfaces. These new findings shed light on the self‐healing mechanism of silicon nanowires and provide new insights into developing high‐lifetime and high‐security semiconductor devices. Abstract : The automatic self‐healing in silicon nanowires is demonstrated by in situ transmission electron microscopy tensile tests. The self‐healing mechanism and factors governing the self‐healing efficiency are revealed by a combination of atomic‐resolution characterizations and atomistic simulations. The results provide new insights into developing high‐lifetime and high‐security semiconductor devices.